5(.666y+1.333)-4y=3

Simple and best practice solution for 5(.666y+1.333)-4y=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(.666y+1.333)-4y=3 equation:


Simplifying
5(0.666y + 1.333) + -4y = 3

Reorder the terms:
5(1.333 + 0.666y) + -4y = 3
(1.333 * 5 + 0.666y * 5) + -4y = 3
(6.665 + 3.33y) + -4y = 3

Combine like terms: 3.33y + -4y = -0.67y
6.665 + -0.67y = 3

Solving
6.665 + -0.67y = 3

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6.665' to each side of the equation.
6.665 + -6.665 + -0.67y = 3 + -6.665

Combine like terms: 6.665 + -6.665 = 0.000
0.000 + -0.67y = 3 + -6.665
-0.67y = 3 + -6.665

Combine like terms: 3 + -6.665 = -3.665
-0.67y = -3.665

Divide each side by '-0.67'.
y = 5.470149254

Simplifying
y = 5.470149254

See similar equations:

| (4x-5/2)-(2x-1/6)=x | | 16x+24=7[x+6] | | (.6)y-4(9)=3-2y | | 32+2y=4 | | 3(15)+x=54 | | 54+6x+4(54-3x)=180 | | 2(z+1)-(5z-4)= | | (19b-6)-9(2b+4)=-2 | | 2(2)y+1=(2)y+3 | | 9x-8=16x+27 | | 12x+2.6=6.8x | | 54=3y+x | | 54=3x+y | | 2(x+9)=30+18 | | (19+3)2=x | | 5/4k=5 | | 54-3(45)= | | 5-2(4x-2)+2x= | | xa+5=7x+b | | -9(x+4)+2x+5=6x+11 | | Y=3*X+2 | | 3(45)+x+6(45)+4x=180 | | 4xy+5xy-3xz-2xy+xy+3xz= | | 8x+6-9x=2-y-15 | | 8-10p+4+8p= | | z(3+2i)=iz+2 | | 2(x+5)+5=2x+9 | | 3x-250=2858 | | 2x+15=385/(x+1) | | 3x+54-3x+6x+4(54-3x)= | | (x+3)(x^2+2x+6)=0 | | 1/16x-3/4y=-1 |

Equations solver categories